Framework development to identify the impact of green building attributes on rental value of commercial properties in Malaysia - Kasim, Rozilah; Umar, Muhammad Akilu; Ishak, Mohd Hafizal; Ariffin, Khadijah Md (American Scientific Publishers, 2018)
Green office buildings offer maximum comfort using less energy to provide a conducive atmosphere for working which invariably encourage production. It provides adequate return on investment over a long period of time having a shorter payback time compared to non-green buildings. Researchers tried to establish the benefit and cost of maintenance of green building based on different parameters. However, this research reviewed different approaches on the issue of green building cost and benefits including building performance as it relates to supply and demand of green building, green building market value, cash flow and market competition. The inspiration for the development of such methodology arose from the need for measuring the impact of green building attributes on rental value of commercial properties in Malaysia. The paper discusses how the impact of green building attributes on rental value can be measured within the context of commercial properties in Malaysia. It further argues that critical assessment need to carried out to determine the attributes which significantly affect the rental value of commercial green buildings.